PRE-OPERATIVE PULMONARY EVALUATION - Khan, Muhammad Aslam; Hussain, Syed Fayyaz (Journal of Ayub Medical College Abbottabad, 2005)
Postoperative pulmonary complications contribute significantly to morbidity and morality in surgical patients. Pulmonary complications occur more frequently than cardiac complications. The complication rates for upper abdominal and thoracic surgery are the highest. A better understanding of the risk factors associated with postoperative pulmonary complications is essential to develop strategies for reducing these complications. In any individual patient the benefit from a surgical procedure should be weighed against the risks it imposes. When possible, stabilization of respiratory status is advisable before surgery. This article reviews patient and procedure related risk factors, clinical and laboratory evaluation for preoperative risk assessment and risk reduction strategies to minimize the complication rates.